UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL DAUN SEREH (Cymbopogon citratus) - dina febrina (Viva Medika, 2018)
ABSTRACT Free radicals are one of the causes of cell damage. Free radicals that have no electrons on the outer layer have very reactive properties, so try to get their partner electrons by attacking the closest stable molecules, such as proteins, lipids, carbohydrates, and DNA and taking electrons from these molecules. Substances that are picked up by electrons will become new free radicals. Efforts are usually done to reduce the reactivity of free radicals and protect against oxidative damage by adding antioxidants. Commonly used antioxidants are synthetic antioxidants, such as BHA (Butyl Hydroxy Anisol), BHT (Butyl Hydroxy Toluene), and TBHQ (Tert-Butyl Hydroxy Quinon). The use of synthetic antioxidants starts to get a negative response because it is thought to have the potential to cause cancer. So that natural antioxidants are increasingly in demand because they are believed to be safer for health. Lemongrass (Cymbopogon citratus) is one of the plants commonly used as spices by the people of Indonesia. However, the use of lemongrass as cooking spices is only located on the stem, while the lemongrass leaves are still a waste. Even though lemongrass leaves are known to contain phenol active compounds which can act as antioxidants. The benefits of lemongrass as an antioxidant are very necessary to make preparations so that it is easier to consume. This study was conducted using the DPPH method with ascorbic acid as a positive control. The results showed that there was a strong antioxidant activity of the citronella ethanol extract which had an IC50 value of 50.3 ppm with ascorbic acid control of 10.4 ppm.